The Role of Human Behavior in Urban Infrastructure Adaptation to Climate Change - Ratriana Bunawardi (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2026)
Climate change brings increasingly complex pressures on urban infrastructure systems, including more frequent flooding events, increased temperature extremes, and disruptions in essential public services. This study examines the role of human behavior as a critical factor in strengthening infrastructure’s adaptive capacity in response to such climatic dynamics. A mixed-methods approach was employed, combining urban residents’ behavioral surveys, analysis of adaptive policy frameworks, and evaluation of critical infrastructure readiness. The findings indicate that risk perception, climate literacy levels, and individual decision-making patterns significantly influence the effectiveness of adaptation strategies. These results affirm that successful adaptation is not solely determined by technology or the physical design of infrastructure, but also by the extent to which communities internalize mitigation practices and adaptive responses. This article recommends multisectoral collaboration, particularly through coordinated policy implementation, community engagement programs, and integrated urban planning among government agencies, urban planners, and communities, to develop more behaviorally responsive adaptation schemes that enhance long-term urban resilience to climate change stressors.